2018
DOI: 10.1002/psc.3079
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the helix‐sense inversion of poly(β‐phenethyl‐L‐aspartate) by two‐dimensional Raman correlation spectroscopy

Abstract: In this study, the transition process of the helix-sense inversion of poly(β-phenethyl-L-aspartate) was investigated by Raman scattering and 2-dimensional correlation spectroscopy. Temperature-dependent Raman spectra were obtained during the helix-sense inversion. The results of 2-dimensional correlation analysis in the spectral regions of 1600-1800 and 3200-3400 cm showed that the intensity changes of the side-chain ester C═O stretching bands occurred prior to those of amide A and amide I bands in the unwindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, most notably, the conformation adjustment of subunit structures can feasibly induce helical inversion. Tunable helical senses of polymers by changing the polarity, donor character, solvation ability of the solvent, or complexation with metal ions have been described. For example, Yashima et al reported that the screw senses of polyphenylacetylene (PPA) bearing achiral phosphonic acid monoesters as the pendant groups were inverted by the adjustment of the asymmetrical position in phosphorus pendants or chiral amine additives in different solvents . Riguera and Freire et al demonstrated that the sp/ap equilibrium in (O)­C–C­(−O) at the pendants was shifted to change the helical senses by complexation with different metal ions. Interestingly, their work involves the cis-trans isomerization of secondary amides induced by changing the donor character of solvents, which would modulate both the elongation and rotation of PPA .…”
Section: Introductionmentioning
confidence: 99%
“…However, most notably, the conformation adjustment of subunit structures can feasibly induce helical inversion. Tunable helical senses of polymers by changing the polarity, donor character, solvation ability of the solvent, or complexation with metal ions have been described. For example, Yashima et al reported that the screw senses of polyphenylacetylene (PPA) bearing achiral phosphonic acid monoesters as the pendant groups were inverted by the adjustment of the asymmetrical position in phosphorus pendants or chiral amine additives in different solvents . Riguera and Freire et al demonstrated that the sp/ap equilibrium in (O)­C–C­(−O) at the pendants was shifted to change the helical senses by complexation with different metal ions. Interestingly, their work involves the cis-trans isomerization of secondary amides induced by changing the donor character of solvents, which would modulate both the elongation and rotation of PPA .…”
Section: Introductionmentioning
confidence: 99%